P55 The occupations associated with COPD risk in the large population-based UK Biobank cohort study. (12th November 2015) - De Matteis, S; Jarvis, D; Hutchings, S; Darnton, A; Rushton, L; Cullinan, P
Abstract : Introduction and objectives: COPD is one of the leading causes of morbidity and mortality worldwide. Exposure to occupational hazards is an important and preventable risk factor. However, the contribution of each occupation to COPD risk in a general population is uncertain. Our aim was to investigate the association of COPD with occupation in a large UK population-based study. Methods: Between 2006 and 2010 the UK Biobank cohort recruited 502, 649 subjects aged 40–69 years. COPD cases were defined by spirometry-based FEV1 /FVC <LLN according to ATS/ERS guidelines. Individual current occupation was coded using the Standard Occupation Classification (SOC) 2000. Prevalence ratios (PRs) and 95% confidence intervals (CIs) of COPD for exposure to each SOC-coded job were estimated using a robust Poisson model adjusted for sex, age, study centre and lifetime tobacco smoking. Results: Of the 353 SOC-coded jobs reported by 228, 614 current working participants several occupations showed a significantly increased COPD risk. The occupations at highest COPD risk were Seafarers (PR = 2.64;95% CI:1.59–4.38), Coal mine operatives (PR = 2.30;95% CI:1.00–5.31), Cleaners (Industrial: PR = 1.96;95% CI:1.16–3.31 and Domestic: PR = 1.43;95% CI:1.28–1.59), Roofers/tilers (PR = 1.86;95% CI:1.29–2.67), Packers/bottlers/canners/fillers (PR = 1.60;95% CI:1.15–2.22), Food, drink and tobacco process operatives (PR = 1.46;95% CI:1.11–1.93), Floorers and wall tillers (PR = 1.41;95% CI:1.00–2.00), Postal workers/couriers (PR = 1.35; 95% CI:1.15–1.59), Labourers in building and woodworking trades (PR = 1.32; 95% CI:1.04–1.68), School mid-day assistants (PR = 1.32; 95% CI:1.01–1.74), and Kitchen/catering assistants (PR = 1.30; 95% CI:1.10–1.53). Associations were similar in analyses restricted to never smokers and to subjects never reporting a doctor's diagnosis of asthma. Conclusions: Selected occupations are associated with increased COPD risk in a large cross-sectional population-based UK study. Further analyses to investigate the underlying occupational hazards are planned. Occupational health surveillance among these occupations should be strengthened.